Translation, adaptation and validation of the Portuguese version of the secretion severity rating scale - Neto, Mariana (2022)
The accumulation of secretions in the hypopharynx, glottis, and/or trachea is a cardinal sign of dysphagia and is of great clinical and therapeutic relevance. To evaluate the residual accumulation of secretions, Murray et al. created the Secretion Severity Rating Scale in 1996. The aim of this study was the translation, adaptation and validation of this scale into European Portuguese through intra- and inter-judge validity and reliability. The translation-retranslation method was used to obtain the Portuguese version of the scale. For validity and reliability, 80 videos were blindly evaluated by 2 experienced clinicians and 40 videos were randomly selected, 10 for each of the severity levels. These 40 videos were subsequently blindly evaluated and re- evaluated 4 weeks apart by 6 ENT physicians, with no previous experience in applying the scale, and by the swallowing evaluation team, with previous experience in applying this scale. Inter and intra- judge agreement ranged from moderate to very good were, with statistical significance. The scale proved to be a reliable and valid instrument for rating the severity of one of the main symptoms of oropharyngeal dysphagia. Notwithstanding the above, its application requires a learning curve.